Aerosol Assisted Solvent Treatment: A Universal Method for Performance and Stability Enhancements in Perovskite Solar Cells. Issue 33 (11th July 2021) - Du, Tian; Ratnasingham, Sinclair R.; Kosasih, Felix U.; Macdonald, Thomas J.; Mohan, Lokeshwari; Augurio, Adriana; Ahli, Huda; Lin, Chieh‐Ting; Xu, Shengda; Xu, Weidong; Binions, Russell; Ducati, Caterina; et al.
Abstract: Metal‐halide perovskite solar cells (PSCs) have had a transformative impact on the renewable energy landscape since they were first demonstrated just over a decade ago. Outstanding improvements in performance have been demonstrated through structural, compositional, and morphological control of devices, with commercialization now being a reality. Here the authors present an aerosol assisted solvent treatment as a universal method to obtain performance and stability enhancements in PSCs, demonstrating their methodology as a convenient, scalable, and reproducible post‐deposition treatment for PSCs. Their results identify improvements in crystallinity and grain size, accompanied by a narrowing in grain size distribution as the underlying physical changes that drive reductions of electronic and ionic defects. These changes lead to prolonged charge‐carrier lifetimes and ultimately increased device efficiencies. The versatility of the process is demonstrated for PSCs with thick (>1 µm) active layers, large‐areas (>1 cm 2 ) and a variety of device architectures and active layer compositions. This simple post‐deposition process is widely transferable across the field of perovskites, thereby improving the future design principles of these materials to develop large‐area, stable, and efficient PSCs. Abstract : A novel, rapid, and scalable treatment method that significantly improves perovskite thin film crystallinity is introduced. Treated perovskite solar cells (PSCs) exhibit enhanced efficiencies, increased stabilities, and improved reproducibility. Versatility and universality are demonstrated using: CH3 NH3 PbI3 (MAPbI3 ) PSCs with thicknesses from 500–1300 nm; large‐area (>1 cm 2 ) devices; a range of device architectures and compositions including Cs0.1 FA0.9 Pb(I0.95 Br0.05 ) devices.